KECEPATAN MEMBACA CEPAT MAHASISWA PROGRAM STUDI PGSD FKIP UNIVERSITAS MUHAMMADIYAH SURAKARTA - Fitri Puji Rahmawati; Nur Ervannudin (Universitas Muhammadiyah Semarang, 2015)
The purpose of this research is to describe the second semester students speed reading courses PGSD FKIP Muhammadiyah University of Surakarta academic year 2014/2015 and the factors that influence it. This type of research in this study is a qualitative research strategy case study. Subjects of this study consisted of students of the second semester Studies Program Elementary School Teacher Surakarta Muhammadiyah University in 2015 and a lecturer of Indonesian Education courses. The research data in the form of the ability to read quickly PGSD students of the second semester of study. The technique of collecting data through observation, interview, and documentation. Validity of the data held by multiple tests, including a test of credibility (internal credibilitas), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results showed that the students of the second semester study program PGSD FKIP Surakarta Muhammadiyah University has had a good read speed, according to the reading speed is the standard of measurement. The average speed reading second semester students Prodi PGSD FKIP UMS 2015 is 206 KPM. There are two factors that affect, namely internal factors and external readers, especially environments.Keywords: speed reading, second semester, internal and external factors.